Analisis Kejadian Stunting Ditinjau Dari Status Imunisasi, Riwayat ASI Eksklusif Dan Berat Badan Lahir Di Wilayah Kerja Puskesmas Pante Raya - Dara Hevriandriana; Lumianna Simorangkir; Arfina Rahmi Sitorus; Lasria Simamora (Pusat Riset dan Inovasi Nasional, 2023)
Background: The population of stunted children is 55% in Asia and 39% of the population of stunted children is in Africa. Riskesdas data (2018) shows that the prevalence of stunted toddlers in Indonesia is 30.8%. Based on the 2020 Aceh province health profile data, it is known that stunting under five in Aceh Province is 10.9%, where Bener Meriah Regency is the Third Regency with the highest stunting rate (18%). This study aims to analyze the incidence of stunting in toddlers in terms of basic immunization status, history of exclusive breastfeeding and birth weight. Method: This research is an observational analytical study using a retrospective case control study design conducted in the Pante Raya Community Health Center Work Area in April – June 2022. The sample size was 18 people, a ratio of 1:1 to 36 people using Consecutive sampling. Data analysis included Univariate and Bivariate with the chi square test, using a significance level of 5% (p value <0.05). Results: Research shows that basic immunization is associated with stunting (p value 0.005<0.05) OR 95% CI 0.100 (0.018-0.569); Exclusive breastfeeding is associated with stunting (p-value 0.006<0.05) OR 0.127 (0.027-0.606); while birth weight was not related to stunting (p-value 0.371>0.05) OR 0.438 (0.069-2.762). Conclusion: Providing basic immunization, exclusive breastfeeding is associated with stunting in the Pante Raya health center working area, therefore it is hoped that the relevant health workers will promote more education about exclusive breastfeeding and also basic immunization programs.